The agony of Bun O'Keefe : a novel - Smith, Heather, 1968- (Penguin Teen, 2019)
Fourteen-year-old Bun O'Keefe is kicked out of her hoarder mother's home in Newfoundland and she ends up on the streets of St. John's. A street musician named Busker Boy takes her in, and along with an eclectic group of misfit street people, Bun learns how to appreciate herself and the things that make her unique.